2021
DOI: 10.1021/acsaelm.1c00659
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Electrical Characteristics of Quasi-One-Dimensional ZrTe3 Nanoribbon Interconnects

Abstract: The aggressive scaling of integrated circuits requires both nanoscale device channels and interconnects. The current Cu interconnects suffer from the limitations of both a nonlinear increase in the resistivity and diminishing current-carrying capacity with scaling down below 20 nm. Here, we evaluated the electrical characteristics of ZrTe 3 nanoribbons, which are representative of a special type of quasi-one-dimensional (1D)/two-dimensional (2D) van der Waals materials, as a possible alternative of Cu for next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results of this study will aid the preparation and processing of nanostructured NbS 3 for device incorporation. 5,12,39 Intriguingly, these dynamics reflect the conversion of a quasi-1D quantum material, NbS 3 , into a 2D quantum material, NbS 2 , which is an area of significant interest as the development of low dimensional materials for quantum technologies accelerates. The integration of low kV imaging, UltraSTEM imaging, and EELS analysis provides an ideal platform for such studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study will aid the preparation and processing of nanostructured NbS 3 for device incorporation. 5,12,39 Intriguingly, these dynamics reflect the conversion of a quasi-1D quantum material, NbS 3 , into a 2D quantum material, NbS 2 , which is an area of significant interest as the development of low dimensional materials for quantum technologies accelerates. The integration of low kV imaging, UltraSTEM imaging, and EELS analysis provides an ideal platform for such studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recent work has revealed that quasi-1D transition-metal trichalcogenide nanomaterials can exhibit outstanding properties, such as charge density waves, the ability to support high current densities before breakdown, low levels of electronic noise, and anisotropic optical characteristics, which make them excellent candidates for next-generation device applications. Niobium trisulfide, NbS 3 , is an especially interesting system because its polymorphism stands out among transition-metal trichalcogenides, with up to five NbS 3 crystal structures verified to date. All contain 1D chains of stacked, niobium hexasulfide trigonal prisms assembled into bilayer sheets through interchain Nb···S and S···S interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The mixed valence disparity of Zr in ZrTe 3 , Zr 2+ and Zr 4+ is reduced in doped crystals but superconductivity with large increase in T c emerges only if CDW is suppressed. Since even modest correlations induce considerable scattering anisotropy in ZrTe 2.96 Se 0.04 , 14 and since ZrTe 3 is considered for interconnects in the next generation roomtemperature nanoscale semiconductor technology due to its size-independent low resistivity, high breakdown current density that increases with size reduction, [65][66][67]…”
mentioning
confidence: 99%